1990
DOI: 10.1103/physrevb.41.11214
|View full text |Cite
|
Sign up to set email alerts
|

Supercurrent tunneling between conventional and unconventional superconductors: A Ginzburg-Landau approach

Abstract: We investigate the Josephson tunneling between a conventional and an unconventional superconductor via a Ginzburg-Landau theory. This approach allows us to write down the general form of the Josephson coupling between the two superconductors, and to see which terms are forbidden or allowed by spatial symmetries. The time-reversal symmetry is also considered. We discuss the current-phase relationships, magnetic, and ac effects if we just include this direct coupling to the unconventional superconductor. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…F 1 and F 2 are scalar under the operations of the complete symmetry of the system G including the crystal symmetry D 4h (or C 4v ), time reversal, spin rotation and gauge symmetry [84,75,76]. The interface term F 12 was chosen in the lowest order and so that it generates the correct boundary conditions [63,75,85,84]. Functions g 1 ( n 1 ) and g 2 ( n 2 ) should be invariant under all operations of the symmetry group of the respective half-space.…”
Section: B D-wave Picture Of a π-Junctionmentioning
confidence: 99%
“…F 1 and F 2 are scalar under the operations of the complete symmetry of the system G including the crystal symmetry D 4h (or C 4v ), time reversal, spin rotation and gauge symmetry [84,75,76]. The interface term F 12 was chosen in the lowest order and so that it generates the correct boundary conditions [63,75,85,84]. Functions g 1 ( n 1 ) and g 2 ( n 2 ) should be invariant under all operations of the symmetry group of the respective half-space.…”
Section: B D-wave Picture Of a π-Junctionmentioning
confidence: 99%
“…The free energy functional for Josephson junctions near T c results in the GL equations and the boundary conditions (BC) for them [20][21][22][23][24] . Consider symmetric junctions with a spatially constant width, which is much less than the Josephson penetration length, and with a plane interlayer at x = 0 of zero length within the GL approach.…”
mentioning
confidence: 99%
“…The Josephson tunneling between conventional and unconventional superconductors are also studied by several authors, 23,24,13,25) but they assumed the unitary states for the triplet superconductors.…”
Section: )mentioning
confidence: 99%
“…Fenton 21) and Geshkenbein and Larkin 22) have shown that the Josephson effect between triplet and singlet superconductors can occur due to the spin-orbit coupling. The Josephson tunneling between conventional and unconventional superconductors are also studied by several authors, 23,24,13,25) but they assumed the unitary states for the triplet superconductors.…”
Section: )mentioning
confidence: 99%